THE EFFECT OF LIQUID ASPHALT ON HIGHWAY FLEXIBILITY - Alex Irawan Trianto; Arya Ningsih; Agus Triyono; Wiwid Suryono; Tomi Apra Santosa; Dika Sulmadianti (AKADEMI TEKNIK ADI KARYA, 2023)
The purpose of this study was to determine the effect of liquid asphalt on highway flexibility. This type of research is quantitative research with meta-analysis methods. The data source comes from an analysis of 10 national and international journals indexed by SINTA and Scopus. Process data search through ScienceDirect, Google Scholar, ProQuest and Wiley. The keyword is the effect of asphalt on highway flexibility. Data analysis by calculating the effect size value using the SAP application. The results concluded that there was a significant liquid asphalt on highway flexibility with an average value of effect size ( ES = 0.88) with a high influence category. These findings provide important information for future research into the effect of liquid asphalt on highway flexibility.